2019
DOI: 10.37268/mjphm/vol.19/no.1/art.48
|View full text |Cite
|
Sign up to set email alerts
|

Regional Disparities of Health Center Utilization in Rural Indonesia

Abstract: One indicator to see the quality of health system performance was to look at the disparity in the utilization of healthcare facilities. The research objective was to analyze the disparity between regions in the utilization of health centers in rural areas in Indonesia. The results of the 2013 Basic Health Survey (Riskesdas) were used as analysis material. The 2013 Riskesdas was designed a cross-sectional survey. Respondents obtained 388,598 using the multi-stage cluster random sampling method. Binary Logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 19 publications
0
15
0
3
Order By: Relevance
“…Disparity as a result of this development also affects the accessibility of the community to health service facilities. Regions with good economic movements tend to have good health service facility accessibility [10]. Previous studies that analyzed regional disparities in the use of health services reported that this condition still exists.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disparity as a result of this development also affects the accessibility of the community to health service facilities. Regions with good economic movements tend to have good health service facility accessibility [10]. Previous studies that analyzed regional disparities in the use of health services reported that this condition still exists.…”
Section: Introductionmentioning
confidence: 99%
“…The Papua region is the easternmost region in Indonesia. The best utilization was in the Sumatra region (westernmost region), which was 3.781 times more utilizing health centers than the Papua region [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With Indonesia’s existing geographical conditions, it is challenging for the government to solve. So far, comprehensive health services have been centered in Java; some of the best-advanced healthcare facilities (hospitals) are in Java [ 8 ]. The Java region is a benchmark for success for other areas in Indonesia, including models for policies addressing gaps in primary healthcare utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia merupakan negara kepulauan sehinggamenyebabkan terjadinya kesenjangan pelayanan kesehatan antara perkotaan dan pedesaan (Laksono & Wulandari, 2019).Salah satu masalah yang timbul dari kesenjangan tersebut adalah tingginya Angka Kematian Ibu (AKI). AKI pada tahun 2015 adalah 305 per 100.000 kelahiran(Kementerian Kesehatan Republik Indonesia, 2017).Jika dilihat menurut pulau, pada tahun 2015 wilayah Nusa Tenggara, Maluku dan Papua memiliki AKI sebesar 489 per 100.000 kelahiran.…”
unclassified